PEMANFAATAN LAHAN PEKARANGAN SEMPIT DALAM PEMBERDAYAAN EKONOMI MELALUI BUDIDAYA TANAMAN IPOMOEA AQUATICA DAN AMARANTHUS DENGAN METODE VERTIKULTUR DI PANTI ASUHAN PUTRA MUHAMMADIYAH KABUPATEN SINTANG - Sari, Wulan Purnama; Hudzaifah, Yasir; Yeni, Yeni; Susilo, Joko; Putra, Kiki Pradana; Ravinazan, Ravinazan; Aqila, Mu’Amar Zaki (Jurnal Abdi Insani, 2024)
Vertical farming is an example of urban farming, defined as a technique for cultivating plants vertically with tiered planting to maximize land use for crop production. Utilizing home gardens can be an essential part of supporting food security because the quantity and quality of family food needs can be adequately met. Nutritious and safe food supplies can be regularly provided from home gardens. The goal of this community service activity is to empower partners (the Muhammadiyah Sintang Orphanage) in utilizing narrow yard spaces through plant cultivation using vertical farming methods, as well as to enhance the partners' knowledge and skills in economic empowerment at the Muhammadiyah Sintang orphanage. The methods used in this community service include focus group discussions, counseling, socialization, and demonstrations of vertical farming methods. The result of this activity was a 75% increase in the knowledge of the orphanage children, from an initial 63% understanding of utilizing narrow yard spaces with vertical farming methods, which is expected to raise awareness of the importance of utilizing narrow yard spaces.